Characterization and microhardness of Co−W coatings electrodeposited at different pH using gluconate bath: A comparative study. (10th January 2013) - Bera, Parthasarathi; Seenivasan, H.; Rajam, K. S.; Shivakumara, C.; Parida, Sanjit Kumar
Abstract : Electrodeposition of Co–W alloy coatings has been carried out with DC and PC using gluconate bath at different pH. These coatings are characterized for their structure, morphology and chemical composition by X‐ray diffraction, field emission scanning electron microscopy, differential scanning calorimetry and X‐ray photoelectron spectroscopy (XPS). Alloy coatings plated at pH8 are crystalline, whereas coatings electrodeposited at pH5 are nanocrystalline in nature. XPS studies have demonstrated that as‐deposited alloy plated at pH8 with DC contain only Co 2+ and W 6+ species, whereas that alloy plated at pH5 has significant amount of Co 0 and W 0 along with Co 2+ and W 6+ species. Again, Co 2+ and W 6+ are main species in all as‐deposited PC plated alloys in both pH. Co 0 concentration increases upon successive sputtering of all alloy coatings. In contrast, mainly W 6+ species is detected in the following layers of all alloys plated with PC. Alloys plated at pH5 show higher microhardness compared to their pH8 counterparts. Copyright © 2013 John Wiley & Sons, Ltd.